The Role of Information Technology in Improving Human Resources Career Development - Efa Wahyu Prastyaningtyas; Abu Muna Almaududi Ausat; Lili Fadli Muhamad; M. Indre Wanof; Suherlan Suherlan (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The ubiquity of information technology in contemporary society has rendered it an indispensable component across a wide. The significance of information technology in the advancement of human resource careers is progressively gaining momentum in the current era of globalisation and rapid technological development. The impact of information technology on the business environment has resulted in significant changes in the management of human resources within organisations. The objective of this investigation is to examine the influence of information technology on the progression of HR careers, investigate the related obstacles and prospects, and furnish pragmatic recommendations for enterprises to proficiently adopt and execute information technology in HR career development. The central focus of this inquiry is predominantly qualitative in character. The methodology of acquiring data entails a rigorous approach of observing and documenting data, which is then subjected to analytical techniques such as data reduction, visualisation, and inference to extract significant findings. The research findings indicate that the utilisation of information technology plays a crucial role in enhancing the professional growth of human resources. The field of information technology facilitates convenient retrieval of information, affords avenues for remote education, enables networking among professionals, and offers tools for enhancing productivity. This facilitates the human resources department to augment their skill set, broaden their knowledge base, establish professional connections, and leverage existing career prospects.